Integrating Light‐Harvesting Ruthenium(II)‐based Units into Three‐Dimensional Metal Covalent Organic Frameworks for Photocatalytic Hydrogen Evolution - Han, Wang‐Kang; Liu, Yong; Yan, Xiaodong; Jiang, Yuqin; Zhang, Jiangwei; Gu, Zhi‐Guo (Angewandte Chemie International Edition, 2022)
Three metal covalent organic frameworks (MCOFs), namely RuCOF‐ETTA, RuCOF‐TPB and RuCOF‐ETTBA, were synthesized by incorporating the photosensitive RuII tris(2,2′‐bipyridine) unit into the skeleton. Interestingly, each RuCOF contains three isostructural covalent organic frameworks that interlock together with the RuII centers serving as point of registry. The covalently linked network coupling with uniformly distributed RuII units allowed the RuCOFs to exhibit superior chemical stability, strong light‐harvesting ability, and high photocatalytic activity toward hydrogen evolution (20 308 μmol g−1 h−1). This work illustrates the potential of developing versatile MCOFs‐based photocatalysts from functionalized metal complex building unit and further enriches the MCOFs family. Three‐dimensional metal covalent organic frameworks (3D MCOFs) with stp topology were constructed by integrating ruthenium(II)‐based units in the skeleton, which exhibited superior chemical stability, strong light‐harvesting ability and excellent photocatalytic hydrogen production rate (20 308 μmol g−1 h−1).